Surmounting Nigeria’s present insecurity : essentiality of local governments’ political communication - Okudolo, Ikemefuna Taire Paul; Salawu, Abiodun (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nigeria’s present insecurity situation has compelled various theories aimed at surmounting the condition. However, most of the theories emphasize ethno-religious dimensions than the character of policymaking to overcome the insecurity. Pundits barely deliberate the nexus between Nigeria’s present insecurity and relegation of local governments’ political communication (LGPC) in intergovernmental policymaking relations (IPR) to neutralize the circumstance. Incidentally, the overwhelming victims of Nigeria’s present insecurity domicile within local government jurisdictions. Consequently, the study aims to accentuate what LGPC offers the Nigerian state to overcome the recent insecurity. Its all-encompassing objective is to promote consideration of LGPC in IPR to effectively overwhelm the current insecurity. It eclectically deploys political communication theory, a constructed Functional Intergovernmental Relations Model and political culture theory as its theoretic framework of analysis. The study’s methodological orientation is explorative qualitative research design, based on secondary analyzed textual and interview qualitative data. It finds that non-consideration of LGPC as inputs – utilizing Nigerian local governments’ experiences, advocacies, activisms, human cum material resources and policy suggestions - in the IPR to mitigate the insecurity ultimately worsens the circumstance. Incessant discounting of local government inputs in the problem-solving policymaking schemes by the higher tiers demonstrates why Nigeria's present insecurity remains intractable. The reality of IPR in Nigeria is that feedback of local governments for the resolution of societal disorders like insecurity is habitually disregarded. Conclusively, the study theorizes that Nigeria's present insecurity will continue to exacerbate if local government contributions are not considered in the alleviation dynamics.